Teacher of Holiness The Holy Spirit in Origen's Commentary on the Epistle to the Romans - Moser, Maureen Beyer (Gorgias Studies in Early Christianity and Patristics, 2014)
This book, on the pneumatology of Origen's Commentary on the Epistle to the Romans, illustrates the centrality of the Holy Spirit for his theological project. As both God's exitus into the world and humanity's reditus to God, the Spirit forms the crucial link between Origen's doctrine of God and his spiritual anthropology. Origen's images for the Holy Spirit, understood in the context of second century concepts of 'spirit,' convey the intersection of theology and anthropology in his thought. This book explores Origen's understanding of the multiplicity of spirits found in the Scriptures, with particular emphasis on the Holy Spirit as pivotal to God's outreach into the world